DETERMINASI FAKTOR KEPERILAKUAN DAN KEORGANISASIAN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI LPD - Putu Kepramareni; Luh Putri Mas Mirayani (Faculty of Economics and Business, Universitas Warmadewa, 2026)
The rapid development of information technology makes the effective implementation of an accounting information system (AIS) in financial institutions such as Lembaga Perkreditan Desa (LPD) crucial for producing relevant, timely, and accurate financial information. However, delays in financial reporting still occur in several LPDs in Banjarangkan District, indicating that the effectiveness of the AIS is not yet fully optimal. The purpose of this research is to investigate and provide empirical evidence on whether personal technical skills, technological sophistication, management participation, training, and task complexity influence the effectiveness of accounting information systems in LPDs in Banjarangkan District. This research utilized a purposive sampling technique to select a sample of 80 employees from a population of 115 individuals working across 27 LPD units. The analytical approach adopted for hypothesis testing is multiple linear regression analysis. The main results showed that personal technical skills, management participation, and training had a positive effect on the effectiveness of accounting information systems. Conversely, technological sophistication and task complexity have no effect on the effectiveness of the accounting information systems. The main implication of this study is that LPDs must focus on improving employees' technical skills, increasing management's active participation, and providing regular training to ensure the accounting information system operates effectively and efficiently